How digital leadership adds affective commitment of new generation employees: an affective events perspective - Hongting Li; Futian Li; Junyi Ma; Bo Liu (Frontiers in Psychology)
How do leaders’ responses to the digital era affect new generation employees’ affective commitment? As digital leaders have led to new ways of distributing digital resources and building virtual relationships, employees are facing a shift in the way of interaction, which influences their affective response to organizations. This study aims to understand how digital leaders interact with new generation employees to influence changes in employees’ affective commitment to organizations. We have developed a chain mediating model and tested it on data collected from 408 new generation employees working in China. Ultimately, we found that digital leadership is associated with more positive changes in new generation employees’ affective commitment. Furthermore, both employee empowerment and employee voice behavior mediate the relationship between digital leadership and affective commitment, forming a chain mediation mechanism in this relationship. We conclude with a discussion of theoretical implications and practical applications.